THE IMPLEMENTATION OF SIMPLE PRESENT VERB AND VOCABULARY MASTERY IN TEACHING WRITING DESCRIPTIVE TEXT - Kartika Zakiah Darajat (Universitas Indraprasta PGRI, 2021)
Abstract: The research aims to understand the effects of simple present verb and vocabulary mastery on students' writing skills in the descriptive text at state vocational high schools in Tangerang Regency. The method used in this research is a survey method. The research shows: There are any significant effects of simple present verb mastery and vocabulary mastery jointly towards students' writing skill in descriptive Text at State Vocational High Schools in Tangerang Regency. It is proved by the result value Sig = 0,000 < 0,05 and F observed = 191,873. It can be concluded that the simple present verb variable and vocabulary significantly influence students' writing skills in the descriptive text at state vocational high schools in Tangerang Regency.Keywords: simple present verb mastery, vocabulary mastery, students' writing skill in descriptive text.